IMPACT OF OVARIAN STATUS AND HARVESTING METHOD ON OOCYTE COLLECTION FROM BUFFALO OVARIES - CHAUDHARI, CF; DERASHRI, HJ; MODI, LC; CHAUDHARI, NF; KHASATIYA, CT; TYAGI, KK (The Indian Journal of Animal Reproduction, 2017)
The impact of presence or absence of corpus luteum (CL) in a buffalo ovary and the oocyte harvesting methods viz., follicle aspiration and ovarian slicing on oocyte collection was investigated. The oocyte recovery rate as well as the per cent oocyte retrieved out of total visible follicles from ovaries with CL and without CL was higher (p<0.05) in slicing than aspiration. In brief, the ovarian slicing is superior over follicle aspiration method to obtain higher number of oocytes from buffalo ovaries and is even better than aspiration in ovaries without CL.